Project Dorothy [videorecording (DVD)] - Dezarn, Tim; Budron, Adam; Scott, Olivia; Harris, Danielle (Gravitas Ventures, 2023)
A pair of criminals activate and AI system known as DOROTHY and must prevent it from breaking free into the world.